Effects of Mo back-contact annealing on surface potential and carrier transport in Cu2ZnSnS4 thin film solar cells. Issue 105 (31st October 2016) - Kim, Juran; Kim, Gee Yeong; Jo, William; Yang, Kee-Jeong; Sim, Jun-Hyoung; Kim, Dae-Hwan; Kang, Jin-Kyu
Abstract : Mo annealing temperature of 500 °C enhances the electrical properties of CZTS absorber, leading to better device performance. Abstract : The effects of Na on Cu2 ZnSnS4 (CZTS)-based solar cells have been examined with respect to surface potential and carrier transport. The Mo back-contact was annealed in a furnace for 10 minutes under a nitrogen atmosphere at different temperatures and CZTS thin films were subsequently grown by sputtering and sulfurization. The thickness of MoS2, formed during the sulfurization process, decreased as the Mo annealing temperature increased. Interestingly, the Na contents diffused from soda lime glass has increased as well. The current and surface potential near CZTS grain boundaries were investigated by Kelvin probe force microscopy (KPFM) and conductive atomic force microscopy (C-AFM) were used. Surface current increased with increasing annealing temperature and surface potential increased up to approximately 50 mV near GBs, which led to inhibition of electron–hole recombination and an increase in minority carrier collection near GBs. This observation explains the improvement of solar cell open circuit voltage ( V OC ) and current density ( J SC ).